2011
DOI: 10.1111/j.1365-2729.2011.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

On the design of online synchronous assessments in a synchronous cyber classroom

Abstract: Online learning has been rapidly developing in the last decade. However, there is very little literature available about the actual adoption of online synchronous assessment approaches and any guidelines for effective assessment design and implementation. This paper aims at designing and evaluating the possibility of applying online synchronous assessments in a formal credit course. Relying on the four dimensions of knowledge taxonomy, this paper describes four different online synchronous assessments for cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 42 publications
0
29
0
8
Order By: Relevance
“…Participants reported that synchronous online tools are beneficial especially for supporting their motivation, time managing, and effective learning. Additionally they consider these tools as supplementary tools for getting inside social communication [24,26,63]. Participants also paid attention to social communication and the importance of being a part of a social community with instant audio-visual tools [64].…”
Section: Resultsmentioning
confidence: 99%
“…Participants reported that synchronous online tools are beneficial especially for supporting their motivation, time managing, and effective learning. Additionally they consider these tools as supplementary tools for getting inside social communication [24,26,63]. Participants also paid attention to social communication and the importance of being a part of a social community with instant audio-visual tools [64].…”
Section: Resultsmentioning
confidence: 99%
“…Chao, Hung, and Chen (2012) described them as traditional learning, asynchronous online learning and synchronous online learning. The learning through real-time interaction among learners themselves, and between learners and teachers using wikis, forums and chats is referred as Synchronous learning.…”
Section: Definition Of Synchronous and Asynchronous Communication In Ictmentioning
confidence: 99%
“…Their comments were in general positive, especially on ease-of-use and its usefulness during the learning process to diagnose the level achieved. On the other hand, there were also some criticisms, especially in terms of clarity of the questions (when the teacher was not present) and of the rigidity of the automatic scoring (Chao et al, 2012). This certainly could be the cause of the poorer perception of F3-Assessment than the other ones.…”
Section: Resultsmentioning
confidence: 99%
“…Some form of credit is often given for CBA, and electronic feedback is offered to students either in the form of a grade or with more extensive comments (Wilson & Scalise, 2006). By means of automatic correction, immediate scoring, instant feedback and adaptive testing, continuous assessment or training can be applied without overloading the teacher (Bain, 2004;Chao, Hung, & Chen, 2012;Gipps, 2005;Hwang, Hsu, Shadiev, Chang, & Huang, 2015;Jordan & Mitchell, 2009;Kuo & Wu, 2013;Pacheco-Venegas, López, & Andrade-Aréchiga, 2015), although the reluctance of some educator's to use these systems may be an impediment to the full benefit of their advantages (Debuse & Lawley, 2016). Information about students' achievements in ACBA can be exploited for evaluating a blended assessment project (Jassó, Milani, & Pallottelli, 2008).…”
Section: Introductionmentioning
confidence: 99%